Fluorinated solid electrolyte as well as preparation method and application thereof

By adopting the preparation method of lithium oxide and tantalum pentafluoride composite solid electrolyte, a fluorinated solid electrolyte with high ionic conductivity and electrochemical stability is formed, which solves the problems of low conductivity and compatibility of existing fluoride solid electrolytes, and achieves the performance of all-solid lithium batteries with high energy density and high working voltage.

CN119683684APending Publication Date: 2025-03-25SHENGHONG KINETIC ENERGY TECH (TAIZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411877267.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing fluoride solid electrolytes have problems with low ionic conductivity and incompatible with high-voltage positive electrode materials, and it is difficult to meet the needs of high energy density and high operating voltage.

Method used

A composite solid electrolyte of lithium oxide and tantalum pentafluoride is used to form a fluorinated solid electrolyte with high ionic conductivity and electrochemical stability through ball milling and calcining, and a controlled lithium fluoride layer is formed on the surface of zirconia to induce benign growth of SEI film.

Benefits of technology

It achieves a high ionic conductivity of 2.3mS cm-1 and significant electrochemical stability to the high voltage platform, and can provide high capacity and good cycling performance in the voltage range of 2.6 to 4.5V.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005197237600000071
    Figure BDA0005197237600000071
Patent Text Reader

Abstract

The invention provides a fluorinated solid electrolyte as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing tantalum pentafluoride powder and lithium oxide powder, and carrying out ball-milling treatment in a glove box in an inert gas atmosphere to obtain a ball-milled product; and calcining the ball-milled product, and cooling the calcined product to obtain the fluorinated solid electrolyte. According to the method disclosed by the invention, the lithium oxide and tantalum pentafluoride composite solid electrolyte is adopted, so that the electrochemical stability of a high-voltage platform is remarkably improved; in addition, the positive electrode can be further protected by an in-situ formed CEI film rich in LiF; zirconium oxide is used as a carrier of the solid electrolyte, a controllable lithium fluoride layer is formed on the surface of the solid electrolyte, and benign growth of the SEI membrane is induced; and the all-solid-state lithium battery prepared from the coating-free high-voltage LCO positive electrode material realizes the high capacity of 180mAh g <-1 > and the good capacity retention rate of 81% after 300 cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion solid-state batteries, and in particular relates to a fluorinated solid electrolyte and a preparation method and application thereof. Background Art

[0002] The global trend of electrification has put forward strict requirements on the safety, energy density and operating temperature of traditional lithium-ion batteries. Unlike traditional lithium-ion batteries, all-solid-state lithium batteries using non-flammable solid electrolytes have the advantages of enhanced safety performance, use of metallic lithium as the negative electrode, wide operating temperature range and reduced packaging requirements, making them promising candidates for the next generation of battery technology. As a key component in non-flammable solid electrolytes, they occupy an important position in this research field. So far, some sulfide electrolytes (such as Li 10 GeP2S 12 ) have achieved impressively high ionic conductivities exceeding 10 mS cm -1 However, most of them have narrow electrochemical windows and are incompatible with common cathode materials such as LiCoO2 (LCO). To address these problems, a series of halogen solid electrolytes have been developed and have shown competitive ionic conductivity (>1mS cm -1 ) and good electrochemical stability with uncoated 4V-class cathode materials.

[0003] Despite these advances, the growing demand for higher energy density is driving the pursuit of higher operating voltages. For example, conventional LCO cathodes can only deliver about 120 mAh g when charged to 4.2 V. -1 The improved LCO cathode with a higher operating voltage of 4.5 V can achieve about 180 mAh g -1 However, most previously reported halogen SEs can only provide about 4.2-4.3 V vs Li + / Li, because when this level is exceeded, it will be oxidized and may form metal chlorides and Cl2. Theoretical calculations show that fluorides have superior anti-oxidation stability compared to other halides, oxides and sulfides, and their stability even exceeds 6V vs Li+ / Li. This is because fluorine has the strongest electronegativity, which enables it to resist oxidation. At the same time, fluorine-containing or fluorinated cathode-electrolyte interfaces formed in situ are generally considered to be beneficial for high-voltage cathode materials due to their electrochemical stability and ability to transport lithium ions.

[0004] However, the fluorination of fluoride solid electrolytes (SEs) remains challenging. Although some fluorides have been predicted to have high lithium ion conductivity, no practical fluoride solid electrolytes have been developed to date. Most reported fluoride solid electrolytes suffer from low ionic conductivity (<10 -2 mxD -1 ) may be due to F - and Li + The strong ionic bond between them hinders Li + mobility in the crystal structure. Even those partially doped with F - The ion-based double-halogen solid electrolyte can only reach an insufficient level (10 -1 mxD -1 ) conductivity. In addition, although some fluorinated ceramic solid electrolytes show enhanced electrochemical stability, the use of high-voltage cathodes such as 4.5 V LCO in all-solid-state lithium-sulfur secondary batteries with satisfactory performance is rarely reported.

[0005] Therefore, it is urgent to develop a new fluorinated solid electrolyte for use in lithium-ion solid-state batteries. Summary of the invention

[0006] Based on the defects of the prior art, the first object of the present invention is to provide a method for preparing a fluorinated solid electrolyte; the second object of the present invention is to provide a fluorinated solid electrolyte prepared by the preparation method; the third object of the present invention is to provide an application of the fluorinated solid electrolyte in the preparation of a lithium-ion solid-state battery; the fourth object of the present invention is to provide an all-solid-state lithium battery comprising a fluorinated solid electrolyte and an uncoated high-voltage LCO positive electrode material.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] In one aspect, the present invention provides a method for preparing a fluorinated solid electrolyte, the method comprising the following steps:

[0009] Step 1, mixing tantalum pentafluoride powder and lithium oxide powder, and performing ball milling treatment in a glove box under an inert gas atmosphere to obtain a ball milling product;

[0010] Step 2: calcining the ball milled product, and cooling the calcined product to obtain a fluorinated solid electrolyte.

[0011] In the preparation method of the present invention, lithium oxide and tantalum pentafluoride composite solid electrolyte are used, which shows significant improvement in the electrochemical stability of the high-voltage platform while still having 2.3mS cm -1 high ionic conductivity; in addition, the LiF-rich CEI film can be formed in situ to further protect the positive electrode.

[0012] In the above preparation method, preferably, in step 1, the ball milling treatment uses zirconium oxide balls, and the zirconium oxide balls are placed in the glove box and mixed with tantalum pentafluoride powder and lithium oxide powder.

[0013] In the preparation method of the present invention, zirconium oxide is used as a carrier of the solid electrolyte, and the proportion of fluoride is regulated by a limited ratio, thereby forming a controllable lithium fluoride layer on the surface of zirconium oxide to induce the benign growth of the SEI film.

[0014] In the above preparation method, preferably, in step 1, the molar ratio of the tantalum pentafluoride powder to the lithium oxide powder is (0.05-0.2): (0.05-0.25).

[0015] In the above preparation method, preferably, in step 1, the ratio of the mass of the zirconium oxide balls to the total mass of the tantalum pentafluoride powder and the lithium oxide powder is 30-40.

[0016] In the above preparation method, preferably, in step 1, the ball mill speed of the ball milling treatment is 450-550 rpm, and the ball milling time is at least 10 hours.

[0017] In the above preparation method, preferably, in step 1, the inert gas is selected from a combination of one or more of argon, krypton and xenon.

[0018] In the above preparation method, preferably, in step 2, the calcination is carried out in a quartz tube, heated to 550-600° C. at a rate of 4-6° C. / min, and annealed and kept at this temperature for at least 5 hours.

[0019] On the other hand, the present invention also provides a fluorinated solid electrolyte, which is prepared by the above-mentioned preparation method.

[0020] In another aspect, the present invention also provides the use of the above-mentioned fluorinated solid electrolyte in the preparation of lithium-ion solid-state batteries.

[0021] In another aspect, the present invention also provides an all-solid-state lithium battery, which comprises the above-mentioned fluorinated solid electrolyte and an uncoated high-voltage LCO positive electrode material. The all-solid-state lithium battery has a voltage of 2.6 to 4.5 V vs Li + / Li voltage range, including 180mAh g -1 The high capacity and good capacity retention of 81% after 300 cycles.

[0022] Beneficial effects of the present invention:

[0023] (1) In the preparation method of the present invention, lithium oxide and tantalum pentafluoride composite solid electrolyte are used, which shows significant improvement in the electrochemical stability of the high-voltage platform while still having a 2.3 mS cm -1 high ionic conductivity; in addition, the LiF-rich CEI film can be formed in situ to further protect the positive electrode.

[0024] (2) In the preparation method of the present invention, zirconium oxide is used as a carrier of the solid electrolyte, and the proportion of fluoride is regulated by a limited ratio, thereby forming a controllable lithium fluoride layer on the surface of zirconium oxide, inducing the benign growth of the SEI film.

[0025] (3) The all-solid-state lithium battery prepared by using the fluorinated solid electrolyte and the uncoated high-voltage LCO positive electrode material of the present invention has a high voltage at 2.6-4.5V vs Li + / Li voltage range, including 180mAh g -1 The high capacity and good capacity retention of 81% after 300 cycles.

[0026] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail below. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not particularly limit the contents.

[0028] Embodiment 1:

[0029] This embodiment provides a fluorinated solid electrolyte and a preparation method thereof, the preparation method comprising the following steps:

[0030] (1) In an argon-filled glove box containing 1086.4 g of zirconium oxide balls, 27.59 g of tantalum pentafluoride powder and 3.45 g of lithium oxide powder were added.

[0031] (2) After the ball mill jar was sealed, a planetary ball mill was used to perform ball milling at a speed of 500 rpm for 10 h to obtain a ball milled product.

[0032] (3) The ball milled product was collected in an argon-filled glove box and packaged in a quartz tube for heat treatment; the particles were heated to 550°C at a rate of 5°C per minute and annealed at 550°C for 5 h. The collected product was naturally cooled to room temperature to obtain a fluorinated solid electrolyte.

[0033] Embodiment 2:

[0034] This embodiment provides a fluorinated solid electrolyte and a preparation method thereof, the preparation method comprising the following steps:

[0035] (1) In an argon-filled glove box containing 543.4 g of zirconium oxide balls, 13.80 g of tantalum pentafluoride powder and 1.73 g of lithium oxide powder were added.

[0036] (2) After the ball mill jar was sealed, a planetary ball mill was used to perform ball milling at a speed of 500 rpm for 10 h to obtain a ball milled product.

[0037] (3) The ball milled product was collected in an argon-filled glove box and packaged in a quartz tube for heat treatment; the particles were heated to 550°C at a rate of 5°C per minute and annealed at 550°C for 5 h. The collected product was naturally cooled to room temperature to obtain a fluorinated solid electrolyte.

[0038] Embodiment 3:

[0039] This embodiment provides a fluorinated solid electrolyte and a preparation method thereof, the preparation method comprising the following steps:

[0040] (1) In an argon-filled glove box containing 2173.3 g of zirconium oxide balls, 55.19 g of tantalum pentafluoride powder and 6.90 g of lithium oxide powder were added.

[0041] (2) After the ball mill jar was sealed, a planetary ball mill was used to perform ball milling at a speed of 500 rpm for 10 h to obtain a ball milled product.

[0042] (3) The ball milled product was collected in an argon-filled glove box and packaged in a quartz tube for heat treatment; the particles were heated to 550°C at a rate of 5°C per minute and annealed at 550°C for 5 h. The collected product was naturally cooled to room temperature to obtain a fluorinated solid electrolyte.

[0043] Comparative Example 1:

[0044] This comparative example provides a solid electrolyte and a preparation method thereof, the preparation method comprising the following steps:

[0045] (1) In an argon-filled glove box containing 543.4 g of zirconium oxide balls, 13.80 g of tantalum pentachloride powder and 1.73 g of lithium oxide powder were added.

[0046] (2) After the ball mill jar was sealed, a planetary ball mill was used to perform ball milling at a speed of 500 rpm for 10 h to obtain a ball milled product.

[0047] (3) The ball milling product was collected in an argon-filled glove box and packaged in a quartz tube for heat treatment; the particles were heated to 550°C at a rate of 5°C per minute and annealed at 550°C for 5 h. The collected product was naturally cooled to room temperature to obtain a solid electrolyte.

[0048] Comparative Example 2:

[0049] This comparative example provides a solid electrolyte and a preparation method thereof, the preparation method comprising the following steps:

[0050] (1) In an argon-filled glove box, 13.80 g of tantalum pentachloride powder and 1.73 g of lithium oxide powder were added.

[0051] (2) After the ball mill jar was sealed, a planetary ball mill was used to perform ball milling at a speed of 500 rpm for 10 h to obtain a ball milled product.

[0052] (3) The ball milling product was collected in an argon-filled glove box and packaged in a quartz tube for heat treatment; the particles were heated to 550°C at a rate of 5°C per minute and annealed at 550°C for 5 h. The collected product was naturally cooled to room temperature to obtain a solid electrolyte.

[0053] Test experiment:

[0054] 1. Ionic conductivity measurement:

[0055] The ionic conductivity of the solid electrolyte was evaluated by EIS results. The fluorinated solid electrolyte powder samples prepared in Examples 1 to 3 and the solid electrolyte powder samples prepared in Comparative Example 1 were respectively pressed into discs with a diameter of 1 cm, and acetylene black carbon was added on each side to improve contact. The discs were placed between two stainless steel bars as blocking electrodes, and they were sealed in a model cell in an argon-filled glove box. On the model cell, EIS measurements were performed using a multi-channel potentiostat with a frequency range of 1 Hz to 7 MHz and a voltage amplitude of 10 mV. The experimental results are shown in Table 1 below.

[0056] 2. Measurement of voltage window:

[0057] For the LSV test, the solid electrolyte powder was mixed with acetylene black carbon in a mass ratio of 7:3 using a mortar and pestle. Two stainless steel rods were used to press 70 mg of the fluorinated solid electrolyte powder samples prepared in Examples 1 to 3 above and the solid electrolyte powder samples prepared in Comparative Example 1 into discs in a polytetrafluoroethylene cylinder with an inner diameter of about 10 mm. To avoid incompatibility between the solid electrolyte powder and the lithium metal anode, 50 mg of LPSC solid electrolyte was pressed on one side of the disc. Afterwards, 10 mg of solid electrolyte / carbon composite material was pressed on the other side of the disc. The pressure used to press the powder into the above-mentioned discs was about 300 MPa. Then, a piece of lithium foil was placed on one side of the solid electrolyte as a counter electrode and a reference electrode. All components were sealed in a model cell (a metal mold that can be sealed by tightening the screws to compress the sealing O-ring) in an argon-filled glove box. LSV measurements were performed on the model cell using a multichannel potentiostat, from open circuit voltage (OCV) to relative to Li + / Li at 7 V, with a scan rate of 0.1 mV s -1 The LSV experimental test results are shown in Table 1 below.

[0058] 3. Battery cycle performance test:

[0059] To prepare the solid-state battery, the improved LCO cathode was pressed into a raw sheet, 70 mg of solid electrolyte was pressed into a disc, and In-Li alloy foil was placed on the other side to form a battery. All five components were sealed in a model battery in an argon-filled glove box. The mass loading of the cathode material was about 6.5 mg / cm 2 .

[0060] The battery was charged and discharged at a rate of 0.5C / 0.5C at 25°C using a BlueDian workstation in the voltage range of 2.6 to 4.5V. The battery cycle performance test results are shown in Table 1 below.

[0061] Table 1:

[0062]

[0063] From the experimental results in Table 1, it can be seen that the solid-state battery has a voltage range of 2.6 to 4.5 V vs Li + / Li voltage range, including 180mAh g -1 The high capacity and good capacity retention of 81% after 300 cycles.

[0064] According to the LSV spectrum, fluorine was confirmed to be introduced into the amorphous structure to form Ta-F and Li-F bonds, which greatly enhanced the stability of the solid electrolyte interface and improved the redox stability of the solid electrolyte under high pressure.

[0065] In addition, the ionic conductivity of the solid electrolyte is extremely high at 2.55 mS cm -1 This will greatly increase the lithium ion migration number, enhance the battery's kinetic performance, and promote the release of the initial gram capacity of the positive electrode material.

[0066] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A method for preparing a fluorinated solid electrolyte, characterized in that: The preparation method comprises the following steps: Step 1, mixing tantalum pentafluoride powder and lithium oxide powder, and performing ball milling treatment in a glove box under an inert gas atmosphere to obtain a ball milling product; Step 2: calcining the ball milled product, and cooling the calcined product to obtain a fluorinated solid electrolyte.

2. The preparation method according to claim 1, characterized in that: In step 1, the ball milling process uses zirconium oxide balls, which are placed in the glove box and mixed with tantalum pentafluoride powder and lithium oxide powder.

3. The preparation method according to claim 1, characterized in that: In step 1, the molar ratio of the tantalum pentafluoride powder to the lithium oxide powder is (0.05-0.2): (0.05-0.25).

4. The preparation method according to claim 2, characterized in that: In step 1, the ratio of the mass of the zirconium oxide balls to the total mass of the tantalum pentafluoride powder and the lithium oxide powder is 30-40.

5. The preparation method according to claim 1, characterized in that: In step 1, the ball mill rotation speed of the ball mill treatment is 450-550 rpm, and the ball milling time is at least 10 hours.

6. The preparation method according to claim 5, characterized in that: In step 1, the inert gas is selected from a combination of one or more of argon, krypton and xenon.

7. The preparation method according to claim 1, characterized in that: In step 2, the calcination is carried out in a quartz tube, heated to 550-600° C. at a rate of 4-6° C. / min, and annealed and kept at this temperature for at least 5 hours.

8. A fluorinated solid electrolyte prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the fluorinated solid electrolyte prepared by the preparation method according to any one of claims 1 to 7 or the fluorinated solid electrolyte according to claim 8 in the preparation of lithium-ion solid-state batteries.

10. An all-solid-state lithium battery comprising the fluorinated solid electrolyte according to claim 8 and an uncoated high-voltage LCO positive electrode material.